Boston Coliseum, Dartmouth Street, ca. 1872 - Unknown (Tufts Archival Research Center, 2005)
Elevated view of the Boston Coliseum built on an area southeast of Copley Square that borders on Saint James Avenue, Dartmouth and Clarendon Streets. This view is of the west and southwest elevations. The west facade faces Dartmouth Street with the southwest bordering the tracks for the Boston and Providence Railroad. A bridge over the railroad tracks in in the foreground, the ticket booth is located at the west corner of the structure. People and horse-drawn vehicles are included in the image. There is a wooden fence surrounding the structure. Designed by William Gibbons Preston; coliseum constructed for the International Peace Jubilee, June 17, 1872 - July 4, 1872 . This image is part of the Chandler Hovey Collection. 7 1/4 X 9 1/2 Photographs